Metatranscriptomic analysis of larval guts from field-collected and laboratory-reared Spodoptera frugiperda from the South American subtropical region - McCarthy, Christina Beryl (2015)
This is the first study to report a high-throughput approach integrating gene expression data from Spodoptera frugiperda guts and their associated metatranscriptomes. Our datasets provide information on the potential effects of environmental conditions on the expression profile of S. frugiperda larval guts, their associated metatranscriptome, and putative interactions between them.